Limited effect of environmental stress on cannabinoid profiles in high‐cannabidiol hemp (Cannabis sativa L.). Issue 10 (28th July 2021) - Toth, Jacob A.; Smart, Lawrence B.; Smart, Christine D.; Stack, George M.; Carlson, Craig H.; Philippe, Glenn; Rose, Jocelyn K. C.
Abstract: Hemp ( Cannabis sativa ) is a burgeoning crop, but research‐based information about genetic and environmental effects of cannabinoid production is limited and will be essential for expanded cultivation. There are limited data available about the effect of environmental stressors on cannabinoid content, particularly for tetrahydrocannabinol (THC) in high‐cannabidiol (CBD) hemp. To address this, five stress treatments were applied in a replicated field trial with three high‐CBD hemp cultivars and cannabinoid content was assayed over a 3‐week time‐course spanning floral maturation. Cannabinoid production in terminal inflorescence shoot tip samples of three cultivars was measured under stress imposed by flooding, ethephon, powdery mildew, herbicide, and physical wounding in a split plot design. The treatments had limited effects on cannabinoid levels, with the exception of herbicide treatment which resulted in decreased cannabinoid content. Notably, there was no evidence that any of these stresses caused THC concentration or the ratio of THC to CBD to increase at harvest. Abstract : Hemp ( Cannabis sativa ) is widely grown for cannabidiol (CBD) production, and some sources suggest that environmental stress causes unwanted "spikes" in tetrahydrocannabinol (THC). To test this theory, we applied various stresses to three hemp cultivars and looked at CBD and THC production. These stresses included powdery mildew, ethephon, flooding, herbicide, and physical wounding. We found that compared to a control, the only significant difference in CBD or THC was a decrease in the herbicide treated plants at harvest, with no difference in the CBD:THC ratio for any treatment. This suggests that environmental stress is not a factor in THC "spikes".